A THE REGIONAL MODES OF INTEGRATION OF INTERNALLY DISPLACED PERSONS (TO THE CONCEPT OF CONCEPTUALIZATION) - Zeitullaieva, Elvira (International Scientific Journal Vision, 2019)
In the article for the first time in Ukrainian science an attempt was made to conceptualize the notion of "the regime of integration of internal migrants". The concept of the regional mode of integration of internally displaced persons is defined. The criteria for classification of the regional mode of integration of internally displaced persons are investigated. The experience of implementation of the programs of integration of internally displaced persons in some regions of Ukraine is studied.